Knockdown of timeless Disrupts the Circadian Behavioral Rhythms in Laodelphax striatellus (Hemiptera: Delphacidae). Issue 5 (27th July 2018) - Jiang, Yan-Dong; Yuan, Xin; Bai, Yue-Liang; Wang, Gui-Yao; Zhou, Wen-Wu; Zhu, Zeng-Rong
Abstract: Most living organisms developed the innate clock system to anticipate daily environmental changes and to enhance their chances of survival. timeless ( tim ) is a canonical clock gene. It has been extensively studied in Drosophila melanogaster (Diptera: Drosophilidae) as a key component of the endogenous circadian clock, but its role is largely unknown in some agriculture pests. Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae), an important rice pest, exhibits a robust locomotor rhythm. In the present study, we cloned tim gene ( ls-tim ) from L. striatellus and investigated its function in the regulation of behavioral rhythms. Quantitative real-time polymerase chain reaction revealed a circadian expression pattern of ls-tim under different light conditions with a trough in the photophase and a peak in the late scotophase. After the knockdown of ls-tim via RNA interference (RNAi), the adults showed an earlier onset of locomotor activity under light/dark cycles and became arrhythmic in constant darkness. ls-tim RNAi also abolished the timing of adult emergence that normally occurs in the early photophase. These results suggest that ls-tim is essential for the light-entrained circadian rhythms in L. striatellus and provide more insights into the endogenous clock network underlying the behavioral and physiological rhythms of this insect.